The impact of welfare benefits on the location choice of refugees testing the Welfare Magnet Hypothesis - Fanny Dellinger; Peter Huber (Austrian Institute of Economic Research (WIFO), 2021)
This paper analyses the influence of welfare benefit levels on migrants' location choices within their host country and thus provides a rare empirical test of the Welfare Magnet Hypothesis. In Austria, asylum seekers are distributed across federal states according to a quota, but once they are granted protection, they are free to move wherever they want. Welfare benefit levels for refugees vary over states depending on a person's protection status and - due to a series of welfare benefit reforms at the state level - over time. This institutional structure allows to causally identify the effect of welfare benefit differentials on refugees' first autonomous location choice. We employ two complementary identification strategies, the first is based on variation over states and protection-status groups. The second is based on the welfare reforms at the state level and exploits variation over states, groups and time. The results provide evidence in favour of the Welfare Magnet Hypothesis.
Keywords: 330; The Welfare Magnet Hypothesis; Refugees; Natural Experiment